Religiusitas dann motivasi belajar pelajaran Agama Islam pada Siswa Sekolah Menengah Pertama - Aditya Surya Firmansyah; Adnani Budi Utami; Karolin Rista (INNER: Journal of Psychological Research, 2022)
Abstract The purpose of this study was to determine the relationship between religiosity and motivation to learn Islamic lessons in students of SMPN 29 Surabaya. In this study there are two variables, namely the variable (Y) is learning motivation and the variable (X) is Religiosity. The hypothesis in this study is that there is a positive relationship between religiosity and learning motivation. The participants of this study were 153 junior high school students. This study uses a quantitative approach to test the proposed research hypothesis. The data analysis technique using Pearson's product moment utilizes the assistance of the Statistical Package for the Social Sciences (SPSS) version 22 for windows program. The results of the correlation analysis between religiosity and learning motivation using Pearson's product moment obtained a score of rxy = 0.620 with a significance value of p = 0.000 (p>0.05). This means that there is a significant relationship between the variables of religiosity and learning motivation. Keywords: Religiosity, Learning Motivation